Analisis Pembelajaran Magnet & Lingkungan Alam dengan Mengambil Contoh dalam Krhidupan Sehari-Hari pada Siswa Kelas IV-A di SD MIS AL-QUBA - Rendi Prilandi; Suyit Ratno; Deva Maria Pangaribuan; Dinda Prati Dina Arsah; Enjel Anatasia Hutabarat; Fajra Lativa Asri; Haris Steven Siregar; Sazkyla Nur Efendi (Jurnal Bintang Pendidikan Indonesia, 2025)
The purpose of this study was to evaluate how effective magnet and natural environment learning is with a contextual approach by providing examples from the daily lives of grade IV-A students at SD MIS AL-QUBA. To collect data, this study used a quantitative approach that used observation, interviews, and test questions. The results showed that the use of real examples from everyday life, such as the use of magnets in household items and how ecosystems interact with each other, can improve students' understanding of science concepts. Direct experience-based learning strategies can also increase student engagement and interest in lessons. Therefore, magnet learning in the natural environment and a contextual approach can help students better understand science concepts in elementary school.